Prints in Rhythm - Leonelli, Giulia (IMPACT Printmaking Journal, 2024)
This paper will introduce my research in the field of printmaking by observing my body of work realised over recent years. Utilising the theoretical approach developed in my doctoral thesis Entendre le pictural (published in 2017). I will defend the rhythmic qualities of printmaking, focusing on the creative process, as well as considering the hanging and installation of a series of prints. First, let’s consider the meaning of this title Entendre le pictorial. The title sheds light on both my reflection on art and my printmaking practice. Entendre in French carries a double meaning: it is the verb form of the word that means to hear and listen; at the same time, it means to understand and consider. This double entendre, when applied to visual arts, suggests a kind of experience that unfolds in space and time, a physical dimension where art is heard and considered, then understood and felt in its scale. The word Pictural in the title refers to the painterly qualities pursued in my work, having been first trained as a painter. Approaching printmaking, this pictorial quest certainly echoes the use of colour and chromatic research as a fundamental part of the creative work. But the main reason I define my printmaking practice as pictorial lies with the abstract patterns and shapes that spring into being as rhythm rather than structure, always seeking to suggest movement and inconsistency. In this sense, the pictorial echoes the painterliness concept defended by art historian Heinrich Wölfflin as a peculiar characteristic of Baroque art in its quest for open and irregular shapes.